2021
DOI: 10.1002/brb3.2164
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms are related to pain and frailty but not cognition or delirium in older surgical patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
(38 reference statements)
0
30
2
Order By: Relevance
“…Furthermore, we used open-field tests to examine the effect of dexmedetomidine treatment on animal behavior, because anxiety and depression are also cognitive symptoms of POCD. [ 34 , 35 ] The data of total distance showed that dexmedetomidine administration did not reduce animal activity; however, surgery significantly reduced the time spent in the center and the bout time in the center ( Figure 7(a) ). Dexmedetomidine abolished this phenomenon, and this effect of dexmedetomidine was reversed by miR-103a-3p inhibitor treatment (Figures 7(b) and 7(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we used open-field tests to examine the effect of dexmedetomidine treatment on animal behavior, because anxiety and depression are also cognitive symptoms of POCD. [ 34 , 35 ] The data of total distance showed that dexmedetomidine administration did not reduce animal activity; however, surgery significantly reduced the time spent in the center and the bout time in the center ( Figure 7(a) ). Dexmedetomidine abolished this phenomenon, and this effect of dexmedetomidine was reversed by miR-103a-3p inhibitor treatment (Figures 7(b) and 7(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…Good surgical effect also helps to improve the anxiety and depression of patients [ 15 ]. A study shows that for patients undergoing elective non cardiac surgery, their preoperative anxiety and depression symptoms are related to their physical weakness [ 16 ]. Another study on cardiac surgery shows that the frailty is related to the perioperative psychological state of patients undergoing cardiac surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when Ren et al examined risk factors for postoperative delirium among 263 patients undergoing elective orthopedic surgery, those diagnosed with anxiety were found to be significantly more at risk of postoperative delirium [ 9 ]. Interestingly, in a retrospective analysis of 167 patients, there was no association between preoperative or new‐onset postoperative depression and anxiety symptoms diagnosed using HADS-A and the incidence of postoperative delirium [ 10 ]. This study controlled for those with pre-existing diagnoses of mental disease, and thus Wang et al proposed episodes of preoperative anxiety may increase perceptions of surgical pain and frailty but not cognitive declines [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a retrospective analysis of 167 patients, there was no association between preoperative or new‐onset postoperative depression and anxiety symptoms diagnosed using HADS-A and the incidence of postoperative delirium [ 10 ]. This study controlled for those with pre-existing diagnoses of mental disease, and thus Wang et al proposed episodes of preoperative anxiety may increase perceptions of surgical pain and frailty but not cognitive declines [ 10 ]. In a retrospective analysis of 183 patients who underwent temporal lobe surgery for epilepsy, those with anxiety were not found to be at increased risk of postoperative seizure or convulsion reoccurrence but were found to report more auras than matched patients without anxiety [ 11 ].…”
Section: Discussionmentioning
confidence: 99%